Proteome profiling of evolved methicillin-resistant Staphylococcus aureus strains with distinct daptomycin tolerance and resistance phenotypes - Sulaiman, Jordy Evan; Long, Lexin; Qian, Pei-Yuan; Lam, Henry (Frontiers in Microbiology, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) is a highly dangerous pathogen, and daptomycin has been increasingly used to treat its infections in clinics. Recently, several groups have shown that tolerance and resistance of microbes can evolve rapidly under cyclic antibiotic exposure. We have previously shown that the same tolerance and resistance development occurs in MRSA treated with daptomycin in an adaptive laboratory evolution (ALE) experiment. In the present study, we performed proteomic analysis to compare six daptomycin tolerant and resistant MRSA strains that were evolved from the same ancestral strain. The strain with a higher tolerance level than the others had the most different proteome and response to antibiotic treatment, resembling those observed in persister cells, which are small subpopulations of bacteria that survive lethal antibiotics treatment. By comparing the proteome changes across strains with similar phenotypes, we identified the key proteins that play important roles in daptomycin tolerance and resistance in MRSA. We selected two candidates to be confirmed by gene overexpression analysis. Overexpression of EcsA1 and FabG, which were up-regulated in all of the tolerant evolved strains, led to increased daptomycin tolerance in wild-type MRSA. The proteomics data also suggested that cell wall modulations were implicated in both resistance and tolerance, but in different ways. While the resistant strains had peptidoglycan changes and a more positive surface charge to directly repel daptomycin, the tolerant strains possessed different cell wall changes that do not involve the peptidoglycan nor alterations of the surface charge. Overall, our study showed the differential proteome profiles among multiple tolerant and resistant strains, pinpointed the key proteins for the two phenotypes, and revealed the differences in cell wall modulations between the daptomycin tolerant/resistant strains.